CHALLENGES AND THE FUTURE OF BUSINESS MANAGEMENT TECHNOLOGY - Risanty Marisca (Adisam Publisher, 2024)
The challenges and future of technology in business management is a very interesting and important topic. Technology continues to develop rapidly and plays an increasingly large role in the way businesses are run and managed. The following are some of the challenges faced as well as future developments in business management technology, namely leadership and cultural transformation, data usefulness, cyber security, artificial intelligence and automation, digital customer experience, and work flexibility and mobility. In facing technological challenges in business management, there are several strategies that can be implemented to remain relevant and competitive in an ever-changing market. The future of technology in business management will continue to offer new opportunities and challenges that need to be overcome. Businesses that are able to adopt and utilize technology well will have a significant competitive advantage in an increasingly connected and rapidly changing market. By understanding these challenges and trends, business leaders can be better prepared to face change and leverage technology to achieve competitive advantage in an increasingly complex business environment. This research in-depth investigates the challenges and future of business management technology using a literature review approach. This research discusses the challenges and future of business management technology, the challenges of modern business management with innovative software, strategies for overcoming technological challenges in business, and the implementation of technology for business success.